Preoperative Assessment of Coronary Arteries by Cardiac Computed Tomography in Patients with Lung Cancer - Zhang, Fan; Chen, Jing; Yang, Zhi-Gang; Liu, Han (The Thoracic and Cardiovascular Surgeon, 2020)
Background To retrospectively evaluate characteristics of coronary artery disease (CAD) in patients undergoing lung resection for cancer by using dual-source computed tomography (DSCT), thus increasing our understanding of perioperative evaluation.Methods DSCT coronary angiography was performed for perioperative evaluation in 145 patients with non-small cell lung cancer (NSCLC) due to suspected CAD. The imaging characteristics of CAD including extent, distribution and types of plaques, and luminal stenosis and congenial anomalous including origin of coronary arteries and myocardial bridge (MB) were evaluated and compared by sex, smoking behavior, and pathological types.Results In total, coronary artery plaques were observed in 130 (89.7%) patients. A total of 205 coronary vessels (1.7 ± 1.3 per patient) and 278 segments (2.4 ± 2.3 per patient) were found to have plaques, respectively. The most frequently involved segment were the left anterior descending (LAD) artery (45.4%) and its proximal segment (24.1%) (p < 0.05). Mild narrowing (61.7%) and calcified plaques (52.9%) were most found (all p < 0.001). Types of plaques, luminal narrowing and extent were not significantly different by sex, smoking behavior, or pathological type. Anomalous origination of the right coronary ostium from left sinus was observed in 0.7% of patients. MB was observed in 16.6% of patients.Conclusion Dual-source CT is a useful preoperative noninvasive test for CAD in patients planning to undergo lung resection for cancer.
Keywords: coronary artery disease; lung resection; non-small cell lung cancer; computed tomography